ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH DALAM TOPIK ALJABAR - Ratu Khoirotun Nisa (LPPM Universitas Bina Bangsa, 2022)
This research is a qualitative descriptive study that aims to describe how the ability to understand students' mathematical concepts and the difficulties experienced by students in solving problems, especially in Algebraic material. The subject of this study consisted of 13 class VIII students at one of the junior high schools in Serang City. The research subjects were chosen because they have the ability to understand mathematical concepts in less and very less categories. The research instrument used was a test of the ability to understand mathematical concepts. The results showed that: 1) Most students had the ability to understand mathematical concepts in less categories, namely as many as 11 students with an average score of 41,065 2) Students who had the ability to understand mathematical concepts in very less categories were 2 students with an average score of 35,71 3) Difficulties experienced by students include difficulty in expressing many tribal algebraic concepts, determining variables, determining constants and determining coefficients, distinguishing which examples include one, two or many tribes, specifying or replacing with variables, making models mathematics, determine the calculation operations that are appropriate for the given questions 4) The indicators in this study are indicators that restate a concept, classify objects according to certain characteristics (according to the concept), provide examples and non examples of concepts, present concepts in various forms of mathematical representation